2014
DOI: 10.1021/jz4025707
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of Pt-Skin and Pt-Skeleton Nanostructures in Acidic Media

Abstract: Following a well-defined series of acid and heat treatments on a benchmark Pt3Co/C sample, three different nanostructures of interest for the electrocatalysis of the oxygen reduction reaction were tailored. These nanostructures could be sorted into the "Pt-skin" structure, made of one pure Pt overlayer, and the "Pt-skeleton" structure, made of 2-3 Pt overlayers surrounding the Pt-Co alloy core. Using a unique combination of high-resolution aberration-corrected STEM-EELS, XRD, EXAFS, and XANES measurements, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 46 publications
5
44
0
Order By: Relevance
“…After 1000 cycles, the peak current densities of MOR are 77, 48, 8.4, 51, and 10 mA cm À2 for 3D Pt 3 Co NWA, 3D Pt NWA, Pt/CB, PtRu/CB, and Pt black, which are about 82 %, 80 %, 33 %, 55 %, and 63 % of their initial values, respectively (Figures 3 d, S15, and S17). [53][54][55] After the ADT test, XPS peak positions of Pt 3 Co NWA are 71.4 eV for Pt 4f 7/2 and 778.2 eV for Co 2p 3/2 , which are close to the initial ones (71.4 and 778.1 eV, respectively; Figures S12 and S19). Furthermore, the final current density of the 3D Pt 3 Co NWA in chronoamperometric measurements is higher than those of PtRu/CB and Pt/CB, indicating that 3D Pt 3 Co NWA is more active and stable than PtRu/CB and Pt/CB (Figures 4 and S18b).…”
Section: Methodssupporting
confidence: 51%
“…After 1000 cycles, the peak current densities of MOR are 77, 48, 8.4, 51, and 10 mA cm À2 for 3D Pt 3 Co NWA, 3D Pt NWA, Pt/CB, PtRu/CB, and Pt black, which are about 82 %, 80 %, 33 %, 55 %, and 63 % of their initial values, respectively (Figures 3 d, S15, and S17). [53][54][55] After the ADT test, XPS peak positions of Pt 3 Co NWA are 71.4 eV for Pt 4f 7/2 and 778.2 eV for Co 2p 3/2 , which are close to the initial ones (71.4 and 778.1 eV, respectively; Figures S12 and S19). Furthermore, the final current density of the 3D Pt 3 Co NWA in chronoamperometric measurements is higher than those of PtRu/CB and Pt/CB, indicating that 3D Pt 3 Co NWA is more active and stable than PtRu/CB and Pt/CB (Figures 4 and S18b).…”
Section: Methodssupporting
confidence: 51%
“…Their central portion is darker than their surface, therefore suggesting a core−shell or a hollow nanostructure. X-EDS global and line-scan analyses as well as elemental maps reveal that (i) hollow-type PtNi/C nanoparticles largely predominate, (ii) Ni and Pt atoms are homogeneously distributed within the metal shell but, as a result of acid leaching, 54 the surface and near-surface of the catalysts are enriched in Pt, and (iii) whatever the Pt:Ni ratio in the metal salt precursor solution, the Ni content estimated by X-EDS over eight different zones is close to 10 at % ( Table 1). The slightly larger Ni content found by atomic absorption spectrometry (AAS) confirms our former results that the electrocatalyst contains a small fraction of solid Ni-rich core@ Pt-rich shell nanoparticles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[15][16][17][18] In particular, Pt is a fascinating catalyst because it effectively promotes the process of ORR. [19][20][21] Recently, the oxidation behavior of Pt 3 Zr (0001) surface was studied by the experiment and rst-principles calculations. 22 They found that the weak localized hybridization between Pt and Zr is benecial to oxidation of Zr metal.…”
Section: -14mentioning
confidence: 99%